Gauge Origin of Double Dark Parity and Implication for Dark Matter - Phung, Dong Van; Duong Van, Loi (Communications in Physics, 2022)
Dark matter must be stabilized over the cosmological timescale, which demands the existence of a stabilizing symmetry, derived by a dark charge, D. The existence of this dark charge may affect the quantization of electric charge, which theoretically shifts the electric charge, thus the hypercharge to a novel gauge extension, SU(3)_CSU(2)_LU(1)_YU(1)_N, where N determines D=T_3+N, similar to Q=T_3+Y. New observation of this work is that the dark charge is broken down to two kinds of dark parity, Z_2 and Z’_2, which subsequently imply three scenarios of dark matter. The relic density and direct detection for the scenario of two-component dark matter are investigated in detail.